Religious motivation and religious lifestyle of Dominican brothers and sisters in Manila - Bhatti, Munawar (Animo Repository, 1992)
This study investigates and presents a descriptive profile of the Dominican Brothers' and Sisters' religious motivation and their self evaluation of the satisfactoriness of their religious lifestyle through the use of two instruments, the Religious Motivation Questionnaire (RMQ) and the Religious Life Self-Evaluation Questionnaire (RLSEQ), respectively. The research participants (N=90) were drawn from the Philippine Province Order of Preachers and 6 out of the 12 Congregations of the Dominican Sisters whose formation houses were within the city of Metro Manila, except for one whose formation house was in San Fernando, Pampanga. The descriptive method of research was the main research design used to determine the profile of both RMQ and the RLSEQ of the Brothers and Sisters. Mean scores were computed. The Pearson r to test the relationship between religious motivation and the respondents' self evaluation of the satisfactoriness of their religious lifestyle and the relationship between tenure and the two latter variables was also computed. The t-test was used to determine whether the Brothers and Sisters significantly differed in religious motivation and their self evaluation of the satisfactoriness of their religious lifestyle.The results show that the Sisters in formation were more motivated in their religious life than the Brothers. They were more inclined toward sacrificial worship in response to an inner calling. In their self evaluation of the satisfactoriness of religious lifestyle, namely, vows, prayer, community life, and ministry, the Brothers and Sisters found their lifestyle satisfactory. In other words, they fulfilled and observed most of the time their religious obligations and responsibilities during the formation period. The Brothers' high esteem was for communitarian aspirations as the harmonizing facet in the brotherhood but the Sisters' high esteem was for prayer as the authentic source of Christian spirituality. There was no significant relationship between the factors of religious motivation and the respondents' self evaluation of the satisfactoriness of their religious lifestyle. The Brothers and Sisters differed significantly on factors of religious motivation but on the self evaluation of the satisfactoriness of religious lifestyle. The Brothers dominated in the area of Christian perfection T (88) = 4.167, p .01, and the Sisters in the areas of social service t (88) The longer the Dominican Brothers' and Sisters' stay in the religious formation, the more they were motivated towards Christian perfection (r=.212, p .05), and the less they became motivated for sacrificial worship in response to an inner calling.